1999
DOI: 10.1097/00004872-199917121-00009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of different dihydropyridines on the expression of adhesion molecules induced by TNF-α on endothelial cells

Abstract: It is concluded that the effect of the DHPs used in this study on adhesion molecule expression is determined first by their lipophilicity and then by their intrinsic antioxidant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 36 publications
2
26
0
8
Order By: Relevance
“…In the same report, it was shown that only benidipine (1 -10 μ M) inhibited TNF-induced ICAM-1 expression. It was also reported that lacidipine, lercanidipine, and amlodipine, but not nimodipine or nifedipine inhibited TNF-induced VCAM-1, ICAM-1, and e-selectin expression in HUVECs (24). In the present study, we confirmed that CV-159 (10 μ M) significantly inhibited TNF-induced expression of e-selectin but not VCAM-1 or ICAM-1 expression in HUVECs.…”
Section: Discussionsupporting
confidence: 87%
“…In the same report, it was shown that only benidipine (1 -10 μ M) inhibited TNF-induced ICAM-1 expression. It was also reported that lacidipine, lercanidipine, and amlodipine, but not nimodipine or nifedipine inhibited TNF-induced VCAM-1, ICAM-1, and e-selectin expression in HUVECs (24). In the present study, we confirmed that CV-159 (10 μ M) significantly inhibited TNF-induced expression of e-selectin but not VCAM-1 or ICAM-1 expression in HUVECs.…”
Section: Discussionsupporting
confidence: 87%
“…Although the direct effect of gp120 on TNF-␣ expression in endothelial cells has not been determined, our data imply that TNF-␣ may not be involved in gp120-mediated endothelial ICAM-1 expression because the expression of VCAM-1 and E-selectin are not affected by gp120 treatment. Unlike HIV-1 gp120, TNF-␣ is a potent inducer for expression of all ICAM-1, VCAM-1, and E-selectin in endothelial cells (Cominacini et al, 1999;Kalogeris et al, 1999). In glial cells, inclusion of a neutralizing antibody against TNF-␣ does not block gp120-induced ICAM-1 expression, suggesting a direct effect of gp120 on ICAM-1 gene expression (Shrikant et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The calcium channel blockade amlodipine has been shown to limit the progression of arteriosclerosis and atherosclerosis in animals and humans (37,38). Although the mechanisms underlying the direct protective effects of calcium channel blockades on endothelial cell injury are not fully understood, such vasoprotective effects as the amelioration of endothelial dysfunction (39,40) and decreases in the proliferation of vascular smooth muscle cells (41), oxidative stress (37,42), and inflammation (43), are at least in part independent of the blood pressure-lowering effects of these agents. The calcium channel blockade has been shown to ameliorate hypertension and improve NO production in the vasculature and kidneys.…”
Section: Introductionmentioning
confidence: 99%